Assessing vitamin D's impact on pregnancy success: a predictive model for assisted reproductive technology outcomes - Jiang, Songwei; Chen, Zushun; Li, Liuming (Frontiers in Reproductive Health, 2025)
ObjectiveTo investigate the correlation between vitamin D levels and clinical pregnancy rates in infertile women undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) procedures and to assess the utility of vitamin D levels in developing a predictive model for assisted reproductive technology (ART) outcomes.MethodsA total of 188 infertile patients receiving their initial IVF or ICSI treatment at our reproductive center between June 2020 and July 2021 were selected for data collection. Vitamin D levels and other relevant ART-related factors were used to construct a predictive model.ResultThe multivariate regression analysis revealed that several independent variables significantly impacted ART pregnancy outcomes, including infertility age, vitamin D level, reproductive anti-Müllerian hormone, antral follicle count, Gn dose, daily endometrial thickness after human chorionic gonadotropin (HCG) administration, and number of retrieved eggs. The area under the receiver operating characteristic curve for this comprehensive model was 75.34%, with a standard error of 0.045 and p-value of 0.003 (95% confidence interval 0.712–0965). Furthermore, the multivariate regression analysis identified specific independent variables that might influence vitamin D levels, such as the number of embryos obtained, daily endometrial thickness after HCG administration, and clinical pregnancy.ConclusionThe developed predictive model integrating serum 25-Hydroxyvitamin D level and ART-related factors holds significant clinical value in forecasting pregnancy outcomes.